Criminal Responsibility for Juvenile Offenders in Criminal Law - Yen, Trinh Thi; Cam, Le (VNU Journal of Science: Legal Studies; Vol 35 No 3DO - 10.25073/2588-1167/vnuls.4228, 2019)
The article mentions the scientific analysis of the main rules on criminal liability for juveniles in the current Vietnamese criminal law and through it, in terms of continuing to improve some regulations. related violations in the Criminal Code 2015 (due to lack of) proposed a number of specific legislative interpretations of 04 new laws relating to criminal liability for unemployment in the draft of the future Criminal Code after France Fourth classicization.